CEFTA: Trade and growth patterns fifteen years since establishment - Nina Vujanović (The Vienna Institute for International Economic Studies (wiiw), 2023)
This research report investigates the trade and growth benefits of the CEFTA agreement for its members. Although the countries have not reached their end goal of membership of the European Union, the report shows that CEFTA has supported their economic growth. However, there is trade heterogeneity in terms of the extent to which individual countries use CEFTA value added in their manufacturing exports. Less-developed economies seem to rely more on regional (CEFTA) supply chains, while manufacturing-based economies are increasingly coming to rely on EU supply chains. The countries have not built a strong export advantage abroad, as very little of their value added is used in EU exports.
Keywords: B17; F14; F43; F63; 330; CEFTA; trade; supply chains; growth